The synergic effects of presynaptic calcium channel antagonists purified from spiders on memory elimination of glutamate-induced excitotoxicity in the rat hippocampus trisynaptic circuit - Keimasi, Mohammad; Salehifard, Kowsar; Mirshah Jafar Esfahani, Noushin; Esmaeili, Fariba; Farghadani, Arman; Amirsadri, Mohammadreza; Keimasi, Mohammadjavad; Noorbakhshnia, Maryam; Moradmand, Majid; Mofid, Mohammad Reza (Frontiers in Molecular Biosciences, 2023)
The hippocampus is a complex area of the mammalian brain and is responsible for learning and memory. The trisynaptic circuit engages with explicit memory. Hippocampal neurons express two types of presynaptic voltage-gated calcium channels (VGCCs) comprising N and P/Q-types. These VGCCs play a vital role in the release of neurotransmitters from presynaptic neurons. The chief excitatory neurotransmitter at these synapses is glutamate. Glutamate has an essential function in learning and memory under normal conditions. The release of neurotransmitters depends on the activity of presynaptic VGCCs. Excessive glutamate activity, due to either excessive release or insufficient uptake from the synapse, leads to a condition called excitotoxicity. This pathological state is common among all neurodegenerative disorders, such as Alzheimer’s and Parkinson’s diseases. Under these conditions, glutamate adversely affects the trisynaptic circuitry, leading to synaptic destruction and loss of memory and learning performance. This study attempts to clarify the role of presynaptic VGCCs in memory performance and reveals that modulating the activity of presynaptic calcium channels in the trisynaptic pathway can regulate the excitotoxic state and consequently prevent the elimination of neurons and synaptic degradation. All of these can lead to an improvement in learning and memory function. In the current study, two calcium channel blockers—omega-agatoxin-Aa2a and omega-Lsp-IA—were extracted, purified, and identified from spiders (Agelena orientalis and Hogna radiata) and used to modulate N and P/Q VGCCs. The effect of omega-agatoxin-Aa2a and omega-Lsp-IA on glutamate-induced excitotoxicity in rats was evaluated using the Morris water maze task as a behavioral test. The local expression of synaptophysin (SYN) was visualized for synaptic quantification using an immunofluorescence assay. The electrophysiological amplitudes of the field excitatory postsynaptic potentials (fEPSPs) in the input-output and LTP curves of the mossy fiber and Schaffer collateral circuits were recorded. The results of our study demonstrated that N and P/Q VGCC modulation in the hippocampus trisynaptic circuit of rats with glutamate-induced excitotoxicity dysfunction could prevent the destructive consequences of excitotoxicity in synapses and improve memory function and performance.